Efektivitas Program Pemberdayaan Ekonomi untuk Peningkatan Kemandirian Ekonomi Kelompok Tani di Jorong Limo Suku Nagari Sungai Pua Kabupaten Agam (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
This study aims to describe and measure the effectiveness of the Economic Empowerment Program in enhancing the economic independence of farmer groups. Empowerment is carried out through efforts to improve farmers' ability to manage their agricultural businesses better, focusing on education, training, extension services, assistance, and the development of agricultural marketing systems. This research uses a descriptive qualitative approach with a field research method. The data sources used consist of primary and secondary data, collected through observation, interviews, documentation, and questionnaires. The data analysis technique used is thematic analysis. The results of the study show that the empowerment process for farmer groups includes extension services, training, discussions, and field practices. The average achievement score of the economic empowerment of farmer groups is 89.23, indicating that this program is effective in enhancing their economic independence. This program has significant long-term impacts on improving the economic independence of farming communities. Through this program, farmers gain access to various training and extension services that enhance the productivity and quality of agricultural products. The improvement in the quality and quantity of agricultural products can expand markets and increase farmers' income.